2014
DOI: 10.1186/1471-2253-14-113
|View full text |Cite
|
Sign up to set email alerts
|

Does premedication with dexmedetomidine provide perioperative hemodynamic stability in hypertensive patients?

Abstract: BackgroundPerioperative hemodynamic fluctuations are seen more often in hypertensive patients than in normotensive patients. The purpose of our study was to investigate the perioperative hemodynamic effects of dexmedetomidine and midazolam used for premedication in hypertensive patients relative to each other and in comparison to normotensive patients.MethodsOne-hundred-forty female, normotensive or hypertensive patients undergoing myomectomies or hysterectomies. They were randomly enrolled into the subgroups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…For hypertensive patients in long‐term standard treatment (e.g. β ‐blockers), premeditation with dexmedetomidine could provide them with stable perioperative haemodynamics, which is especially important for hypertensive patients . Our study also observed that patients who received dexmedetomidine‐remifentanil at a dose of 0.2 μ g/kg/hour and patients who received midazolam‐remifentanil all exhibited stable haemodynamics during HIFU therapy.…”
Section: Discussionsupporting
confidence: 56%
“…For hypertensive patients in long‐term standard treatment (e.g. β ‐blockers), premeditation with dexmedetomidine could provide them with stable perioperative haemodynamics, which is especially important for hypertensive patients . Our study also observed that patients who received dexmedetomidine‐remifentanil at a dose of 0.2 μ g/kg/hour and patients who received midazolam‐remifentanil all exhibited stable haemodynamics during HIFU therapy.…”
Section: Discussionsupporting
confidence: 56%
“…Dexmedetomidine is a highly selective α 2 -adrenoreceptor agonist that induces sedation providing improved hemodynamic stability without eliciting respiratory depression (10)(11)(12)(13). Previous studies have reported that dexmedetomidine is rapidly and efficiently absorbed after intranasal administration, and is better tolerated compared with intravenous administration (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Earlier reports demonstrated that patients benefit a lot from perioperative application of Dex, such as reduced stress response during incubation and operation, and hemodynamic stability. [9,10] However, the effects of Dex on gastrointestinal function remain controversial. Some researchers demonstrated that Dex could protect intestine from injury caused by intestinal I/R and endotoxemia, [11,12] whereas others found that Dex would prolong the gastric emptying and gastrointestinal transit in the rat.…”
Section: Introductionmentioning
confidence: 99%